Islamic Menstrual Holistic Care Education Class for Young Women during the Covid 19 Pandemic - Aida Ratna Wijayanti; Inna Sholicha Fitriani; Sholihatul Maghfiroh (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
Physical and psychological changes that occur in adolescent girls, especially at the beginning of puberty can affect anxiety which leads to the risk of decreased body immunity. The purpose of this service is that young women can prepare for or undergo puberty and puberty safely, comfortably and can reduce the risk of anemia and decreased endurance, especially during the pandemic Covid-19. The location of the service is at the LKSA Orphanage of Nurus Syamsi Muhammadiyah, Bungkal District, Ponorogo Regency, East Java. Service activities in the form of educational classes with conventional methods, discussions. In the education class, 3 (three) different materials were given, namely 1) Puberty and Akil Baligh, 2) Myths About Menstruation, 3) Thaharoh and Practices During Menstruation. In this educational class, young women are also given blood-boosting multivitamins to prevent anemia during menstruation. After this service activity is carried out, it is hoped that there will be awareness in maintaining cleanliness and health during puberty, especially to reduce the risk of anemia in young women in orphanages during the pandemic Covid-19.